Low reactivity of tumor MUC1-binding natural anti-α-galactoside antibody is a risk factor for breast cancer. Issue 3 (February 2020) - John, Jessy; Cherian, Kurian; Abraham, Thomas; Appukuttan, Padinjaradath S
Natural plasma anti-α-galactoside antibody (anti-Gal) reactivity was reported to vary inversely with the individual's lipoprotein(a) [Lp(a)] size. Since MUC1 mucin over-expressed in tumors bear surrogate peptide ligands for anti-Gal, we examined if high anti-Gal reactivity in small size/high titer Lp(a) individuals correlated with lower incidence of breast cancer. Newer protocol for size determination revealed that Lp(a) in controls were significantly smaller than in breast cancer patients ( P  =   0.0023; n = 46 in either group). Activity per unit plasma volume and specific reactivity (reactivity per unit immunoglobulin) of anti-Gal were significantly lower in cancer patients ( P  = 0.0033). Specific reactivity lower than the mean of controls was a risk factor for breast cancer with odds ratio (OR) 3.2 (95% confidence interval [CI]: 1.368–7.557). Immunochemical staining using fluorescein isothiocyanate-labeled anti-Gal revealed absolute inactivity towards normal cells and strong recognition of cancer cells by the antibody. O-Glycosylation of MUC1, though more frequent than in normal cells, was incomplete in tumor cells as revealed by binding of the O-glycan-specific lectin jacalin, accounting for the access of anti-Gal to its peptide ligand in cancer MUC1. As tumor advanced and MUC1 with increasing affinity for anti-Gal was synthesized by the tumor, the specific reactivity of circulating anti-Gal also increased, apparently due to antigenic stimulation or affinity maturation by the proliferating MUC1, indicating that pre-cancer anti-Gal reactivity in patients should have been much lower than measured after detection of cancer and that lower reactivity of the antibody is a stronger risk factor for breast cancer than indicated by the OR above. Reactivity towards a given group of tumor MUC1 antigens increased in proportion to anti-Gal specific reactivity. Results suggested tumor-specific MUC1 as likely target for anti-Gal-mediated anti-cancer defense and offer infusion of small Lp(a) or high reactivity anti-Gal as possible immunopotentiation measures. Impact statement: This paper offers a molecular explanation for the positive correlation of individuals' lipoprotein(a) [Lp(a)] size with breast cancer incidence, found more pronounced using interference-free assays. It established unambiguously the marked affinity of human anti-Gal antibody towards cancer phenotype of the cell surface MUC1 and inertness towards normal cell MUC1. This selectivity enabled small Lp(a) molecules, known to produce higher specific reactivity anti-Gal by affinity maturation, to achieve more efficient immune defense so that women with specific reactivity lower than the mean value of normal subjects ran cancer risk with odds ratio (OR) above 3.2. However, increasing O-glycosylation and decreasing O-glycan length of MUC1 with tumor advance increased anti-Gal specific reactivity, indicating antigenic stimulation and/or affinity maturation of the antibody by tumor MUC1. Thus, pre-cancer anti-Gal specific reactivity should be lower than that measured on detection and the above OR actually higher. Results suggest small Lp(a) and high specific reactivity anti-Gal infusions as therapeutic options.